Satyra na dogmat? „Strategia przewrotności” w Dogmie Kevina Smitha - LEWANDOWSKA, ZUZANNA (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Satire on dogma? The strategy of subversion in Kevin Smith’s Dogma Religious themes which appear in the cinema in a fashion that differs from the classical view of Bible stories often become problematic for the audience, especially its more religious members, who find such movies blasphemous and sacrilegious. At the same time, it seems that the aim of many such works is not to act against religion, but rather to show the truths of faith in a new perspective. This kind of approach, described as a “strategy of subversion“ based on the affirmation by illusory negation, can be found in the way Kevin Smith created his Dogma (1999). The aim of this article is to examine those aspects of Dogma, which on the one hand undermine the dogmatic character of religion and the commercialization of the Catholic Church, and on the other, expose and emphasize the senses of faith and cultivating religion lying underneath the pop culture in a ostensibly profane form.